Green Human Resources Management In The Sustainability of Diving Tourism Business - Dikri Gifari; Wawan Prahiawan (Journal of Business Technology and Economics, 2024)
Indonesia is an archipelagic country that has great maritime tourism potential, one of which is diving tourism. The great potential must be maintained sustainably so that the tourism business can always exist and have good benefits, so in this research the theme is Green Human Resources Management (GHRM) which is linked to the sustainability of the diving tourism business at the Dive Center as the spearhead of this tourism organizer. GHRM implementation is assessed to measure the extent to which GHRM variables are able to have a positive impact on the sustainability of diving tourism businesses. The aim of this research is to determine the influence of Green Human Resources Management on business sustainability in the diving tourism sector by distributing questionnaires to employees or crew who work at dive centers which results in the behavior and implementation of Green Human Resources Management being able to have a positive impact on business sustainability in the field, and the result in this research is shows that Green Human Resources Management has a positive and significant effect on Business Sutainability at the Dive Center for their business sustainability in the diving tourism sector. This research aims to provide ecological and business benefits so that business sustainability remains so that dive center management continues to provide the best service to customers.